ANALISIS PENGARUH HUMAN CAPITAL TERHADAP KUALITAS AUDITOR (Studi Empiris Pada Bank BRI Kantor Inspeksi Semarang) - Yana Aisyah; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to determine the relationship of human capital that may affect the auditor quality, in which the independent variable consists of formal education level, working experience, professional qualification auditor and continuing professional development. The population of this research are auditor in Bank BRI in Semarang, sample that used amounted to 47 respondents. Method of testing is done by multiple linear regression analysis. Under the normality test, multicollinearity, heteroscedasticity test and test autocorrelation, there not found variables that deviate from the classical assumptions. This shows that the available data are qualified to use the multiple linear regression model. The results have shown that human capital positively affects the auditor quality. Higher levels of education, work experience, level of professional qualification, and the continuing professional development also produced higher auditor quality produced by the company.